Repurposing of eluxadoline as a SARS-CoV-2 main protease inhibitor: E-Pharmacophore based virtual screening, molecular docking, MM-GBSA calculations, and molecular dynamics simulations studies - Magdi A. Mohamed, Alaa F. Alanazi, Waad A. Alanazi, Tilal Elsaman, Malik S. Mohamed, Eyman M. Eltayib (Journal of Applied Pharmaceutical Science, 2024)
This study presents a comprehensive computational approach aimed at repurposing an FDA-approved drug, retrieved from the DrugBank database, as a potential inhibitor of the SARS-CoV-2 main protease, a crucial target for antiviral drug development. Utilizing e-pharmacophore-based virtual screening, molecular docking, MM-GBSA calculations, and molecular dynamics simulations, the key interactions and binding affinities of Eluxadoline, the top-ranked drug, with the target protease were elucidated. The findings provide valuable insights into the molecular mechanisms underlying Eluxadoline’s inhibitory activity against the SARS-CoV-2 main protease, highlighting its potential for combating emerging viral threats. Further experimental validation is recommended to confirm and optimize Eluxadoline’s efficacy, paving the way for its potential clinical application in the ongoing battle against COVID-19. This study underscores the significance of repurposing existing drugs as a promising strategy for urgently needed therapeutics against global pandemics like COVID-19.
Keywords: COVID-19, SARS-CoV-2 main protease, Drug repurposing, CADD, DrugBank, Eluxadoline